W sieci szkolnych gatunków (auto)prezentacyjnych. W poszukiwaniu prototypu - Grzegórzek, Mirosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article is an attempt to outline the cognitively understood web of school genres used for self-presentation. The author is trying to answer the question of which genre takes the place of the prototype model centre and what relations occur between the genres within the web. The starting point for the literary genetics traversing in the linguistic-didactic perspective was the theory of self-presentation as well as both school and extracurricular texts that pursue specified genre patterns. The prototype is a pattern, the exemplary model of something. On the basis of the comparative studies on school genres used for self-presentation and with the help of metaphorical categories of self-presentation gene and the genotype the self-presentation genre it has been concluded that the prototype of the self-presentational genre at school is self-characteristics.
Keywords: prototype; school genres; self-presentation; network model; family resemblance